2015
DOI: 10.1021/ic502515x
|View full text |Cite
|
Sign up to set email alerts
|

Alkane C–H Functionalization and Oxidation with Molecular Oxygen

Abstract: The application of environmentally benign, cheap, and economically viable oxidation procedures is a key challenge of homogeneous, oxidative alkane functionalization. The typically harsh reaction conditions and the propensity of dioxygen for radical reactivity call for extraordinary robust catalysts. Mainly three strategies have been applied. These are (1) the combination of a catalyst responsible for C-H activation with a cocatalyst responsible for dioxygen activation, (2) transition-metal catalysts, which rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
46
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(48 citation statements)
references
References 240 publications
0
46
0
Order By: Relevance
“…In particular,t he degree of cross-linking is expected to vary with the number of vinyl groups in the monomer.D irect metallation using literature procedures afforded [Ag(bmim) 2 ] 2 [Ag 2 Cl 4 ] 2a [46] and Ag[bvbim]Clc omplex 2b in good yield ( Figure 1). 13 CNMR spectra showedt he characteristic carbene signals at 180.7 and 180.9 ppm for 2a and 2b,r espectively. [46][47][48][49][50] The use of silver intermediates precluded any radical polymerization of the vinyl moiety at an earlier stage;s ome other protocols use harsh reactionc onditions under which such unwanteds ide reactions could occur.…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…In particular,t he degree of cross-linking is expected to vary with the number of vinyl groups in the monomer.D irect metallation using literature procedures afforded [Ag(bmim) 2 ] 2 [Ag 2 Cl 4 ] 2a [46] and Ag[bvbim]Clc omplex 2b in good yield ( Figure 1). 13 CNMR spectra showedt he characteristic carbene signals at 180.7 and 180.9 ppm for 2a and 2b,r espectively. [46][47][48][49][50] The use of silver intermediates precluded any radical polymerization of the vinyl moiety at an earlier stage;s ome other protocols use harsh reactionc onditions under which such unwanteds ide reactions could occur.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 1a nd Scheme 2). They were characterizedb y 1 Ha nd 13 CNMR spectroscopy and elemental analysis. All signals were sharp and, again, characteristicc arbene signals around 150 ppm were observed in the 13 CNMR spectrai nC DCl 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14] Amongo xidants used in oxidation reactions, dioxygen (O 2 )i s the greenest, since the product of O 2 reduction is water or hydrogen peroxide. [15] Thus,t ransitionm etal catalysts are utilized for the catalytic oxidation of organic substrates by O 2 , [16][17][18][19][20][21][22][23] wherebyh igh-valent metal-oxo species are generated as reactive intermediates from the oxidation of metal complexes by O 2 with reductants. [15] Thus,t ransitionm etal catalysts are utilized for the catalytic oxidation of organic substrates by O 2 , [16][17][18][19][20][21][22][23] wherebyh igh-valent metal-oxo species are generated as reactive intermediates from the oxidation of metal complexes by O 2 with reductants.…”
Section: Introductionmentioning
confidence: 99%
“…[4] In spite of the dramatic progress, the development of efficient transition metal catalysts for selective oxidative functionalization of inert CÀH bonds, especially that employing oxygen as an environmentally benign and inexpensive terminal oxidant, remains challenging. [5] So far, some promising results in aerobic CÀH oxidation have been demonstrated using Pd-based systems, [6][7][8][9][10][11][12][13] whereas the progress in aerobic CÀH oxidation catalyzed by Pt complexes remains slow. In the early 1980s, Shilov et al demonstrated a proof-of-concept aerobic CÀH oxidation mediated by Pt compounds for the first time.…”
Section: Introductionmentioning
confidence: 99%